Five-Input One-Output Universal Filter Using Simple CMOS OTAs - Knobnob, Boonying; Suksaibul, Pichai; Kumngern, Montree (My University, 2018)
This paper presents a new five-input one-output voltage-mode universal filter using simple operational transconductance amplifiers (OTAs). The circuit uses six OTAs and two grounded capacitors. The circuit can realize low-pass, band-pass, high-pass, band-stop and all-pass filters into one topology. The natural frequency and the quality factor of filters can be electronically controlled by adjusting the bias currents. Also, the circuit possesses high input impedance for all filtering functions. The simulation results have been verified by PSPICE simulations using 0.18 μm CMOS process from TSMC.
Keywords: analog circuit; operational transconductance amplifier; universal filter; voltage-mode circuit